Beyond Namaste: A Cultural Exploration of Nepalese Hospitality Traditions - Sharma, Samik (Nepalese Journal of Hospitality and Tourism Management, 2025)
Nepalese hospitality is a unique and socio-cultural institution deeply rooted in religious values, communal ethics, and social honour. Guided by the principle of Atithi Devo Bhava, “The guest is equivalent to God”, hospitality in Nepal extends beyond simple courtesy to a moral and spiritual duty. This paper intends to explore the historical, religious, and socio-cultural foundations/ dimensions of hospitality in Nepal through examining its manifestations across ethnic, regional, and caste lines. It further aims to analyse how modernisation, urbanisation, and tourism are reshaping traditional hospitality practices. Drawing on academic literature and tourism case studies, the findings reveal a culture of hospitality that is resilient yet adaptable, facing both opportunities and tensions in a globalised era. The study concludes by offering recommendations for tourism planning, promoting gender equity, and preserving cultural heritage.